Covalently anchored 2,4,6-triallyloxy-1,3,5-triazine Pd(II) complex over a modified surface of SBA-15: catalytic application in hydrogenation reaction - Sharma, Priti; Singh, A. P. (RSC Advances, 2014)
Highly efficient and reusable SBA-15-TAT-Pd(II) has been synthesized by anchoring a 2,4,6-triallyloxy-1,3,5-triazine (TAT) complex over the organo-functionalized surface of SBA-15. The physiochemical properties of the organo-functionalized catalyst were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption measurement isotherm, TGA & DTA, solid state C-13, Si-29 NMR spectra, FT-IR, XPS, DRS UV-visible, SEM and TEM. XRD & N-2 sorption were analyzed to find out the textural properties of the synthesized catalyst and confirm that an ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The electronic environment and oxidation state of Pd in SBA-15-TAT-Pd(II) were monitored by XPS and DRS UV-visible techniques. The catalytic activity of the synthesized catalyst SBA-15-TAT-Pd(II) was screened for hydrogenation reactions and shows higher catalytic activity with good turnover numbers (TON) under optimized experimental conditions with maximum conversion (> 99%) and selectivity (100%). The anchored solid catalyst can be recycled efficiently and reused upto five times without major loss in reactivity.